Studi Kelayakan Jalan Lingkar Pangkal Pinang – Batu Bariga Sadai - Indra, Indra Jaya Putra; Nisumanti, Sartika; Baniva, Ratih (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
ABSTRACT The construction of proper road infrastructure is very important to support the economic growth of an area. The spatial planning set by the Provincial Government of the Bangka Belitung Islands plans the construction of the Pangkalpinang – Batu Beriga – Sadai Ring Road. The availability of an adequate road network is expected to help open up the isolation of border areas, thereby improving accessibility and increasing the mobility of the population. This road segment is an important access route for the island region to the Toboali harbor and tourist attractions such as Tanjung Berikat beach and Toboali harbor. The purpose of this research is to analyze the economic and financial feasibility of this road segment by calculating the difference between BOK (Vehicle Operation Cost) and NK (Time Value and Time Saving). The economic aspect is analyzed based on the benefit-cost ratio (BCR) and net present value (NPV) parameters as a feasibility reference. From the analysis results, the recap of the Benefit Cost Ratio value is 10% = 764.32 Benefit Cost Ratio 12% = 782.74 Benefit Cost Ratio 15% = 782.68 IRR 10% = 12.36 IRR 12% = 14.62 IRR 15% = 14.60 NPV 10% = Rp. 1.442.849.450.375.310 NPV 12% Rp.1.410.952.049.481.800 NPV 15% = Rp.1.362.851.291.513.830. Keywords: BOK, Time Value, Net Present Value ABSTRAK Pembangunan infrastruktur jalan yang tepat sangat penting untuk mendukung pertumbuhan ekonomi suatu daerah. Rencana tata ruang yang ditetapkan oleh Pemerintah Provinsi Kepulauan Bangka Belitung merencanakan pembangunan Jalan Lingkar Pangkalpinang – Batu Beriga – Sadai. Tersedianya jaringan jalan yang memadai diharapkan dapat membantu membuka keterisolasian daerah perbatasan, sehingga dapat membuka aksesibilitas, meningkatkan mobilitas penduduk. Ruas jalan ini merupakan akses penting daerah kepulauan menuju pelabuahan Toboali serta objek wisata seperti pantai Tanjung Berikat dan pelabuhan Toboali. Tujuan penelitian ini menganalisis kelayakan Ekonomi dan finansial pada ruas jalan ini dengan menghitung dihitung berdasarkan selisih BOK (Biaya Operasional Kendaraan/Vehicle Operation Cost) dan NK (Nilai Waktu dan Time Saving). Adapun menganalisis aspek ekonomi berdasarkan paramater benefit cost ratio (BCR) dan net present value (NPV) sebagai acuan kelayakan. Dari hasil analisis didapatkan rekapitulasi nilai Benefid Cost Ratio 10% = 764,32 Benefid Cost Ratio 12% = 782,74 Benefid Cost Ratio 15%= 782,68 IRR 10% = 12,36 IRR 12% = 14,62 IRR 15%= 14,60 NPV 10% = Rp. 1.442.849.450.375.310 NPV 12% Rp.1.410.952.049.481.800 NPV 15% = Rp.1.362.851.291.513.830 Kata Kunci: BOK, Nilai Waktu, Net Present Value.